2007
DOI: 10.2151/sola.2007-024
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Trans-equatorial Monsoon Flow on the Formation of Repeated Torrential Rains over Java Island

Abstract: Torrential rains that repeatedly occurred over Java Island causing widespread floods in late January and early February 2007 coincided with a strong and persistent trans-equatorial monsoon flow from the Northern Hemisphere. While convections develop frequently over the island's mountainous areas in the afternoon, convections over the northern plains are active during the night and morning hours. The strong trans-equatorial monsoon flow with an upper southeasterly wind produces a strong low-level vertical shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 9 publications
9
65
1
6
Order By: Relevance
“…To summarize, a persistent transequatorial monsoonal flow from the Northern Hemisphere occurred in midJanuary prior to and during the extreme precipitation event of 2013 in Jakarta, similar to that reported by Wu et al (2007) as the main cause of the long duration of heavy precipitation that occurred in Jakarta during late January into early February 2007.…”
Section: Occurrence Of a Trans-equatorial Monsoonal Flow From The Norsupporting
confidence: 85%
See 3 more Smart Citations
“…To summarize, a persistent transequatorial monsoonal flow from the Northern Hemisphere occurred in midJanuary prior to and during the extreme precipitation event of 2013 in Jakarta, similar to that reported by Wu et al (2007) as the main cause of the long duration of heavy precipitation that occurred in Jakarta during late January into early February 2007.…”
Section: Occurrence Of a Trans-equatorial Monsoonal Flow From The Norsupporting
confidence: 85%
“…The event ranked with the 1996, 2002, and 2007 flood events in Jakarta as one of the worst floods in recorded history. Wu et al (2007) reported, for the first time, an unusually long duration of heavy precipitation that occurred in Jakarta during late January into early February 2007. Later the case was investigated in detail with a numerical nonhydrostatic model (Trilaksono et al 2011;Trilaksono et al 2012).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Time-lagged ensemble simulations were performed to produce nine members at each output time, and all ensemble members are used in the following analyses. The analysis domain covers the western part of Java Island, Indonesia, and the experimental period includes a flooding event occurred in Jakarta in February 2007 (Wu et al 2007). …”
Section: Size Of Precipitation Areamentioning
confidence: 99%